The Income Distribution and Household Food Security of Beef Cattle Farmers in The Special Region of Yogyakarta, Indonesia - Achmad, Ferdian (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aimed to calculate income and its distribution as well as the food security rate and to analyze factors affecting food security rate of independent and profit-sharing farmers of beef cattle fattening in Special Region of Yogyakarta. An explanatory was used as the method for the research in Gunungkidul, Sleman, Bantul, and Kulonprogo Regencies by quota sampling on 120 independent and 120 profit-sharing farmers. Data were analyzed through income formulation, R/C Ratio, Gini Ratio, cross-classification of food expenditure share and energy consumption (Table of Jonsson and Toole), and ordered logistic model. The research results indicate that the incomes of independent and profit-sharing farmers were IDR1,079,033.00 and IDR1,023,324.00, lower than the Minimum Wage of Special Region of Yogyakarta which amounted to IDR1,337,645.25. The business was still accountable because the R/C ratio had a value larger than one. The values of the Gini Ratio of independent and sharing farmers were 0.310 and 0.219 which categorized as the low-scale unequal income distribution. Food security rates of independent and profit-sharing farmers were 22.5% and 13.33% of food secure, 15.83% and 18.33% of food vulnerable, 40.0% and 38.34% of less-secure food, and 21.67% and 30.0% of food insecure. The determining variables were the price of rice (p<0.01), price of vegetable (p<0.05), price of beef (p<0.01), price of cooking oil (p<0.05), and the price of instant noodle (p<0.01), household income (p>0.05), education dummy (p<0.05), cattle group dummy (p>0.05), the number of family member (p<0.01), and the housewife education (p>0.05).